An investigation of young children’s perceptions of teasing within peer relationships - Debra Harwood; Sandra Bosacki; Kristina Borcsok (International Electronic Journal of Elementary Education, 2010)
The paper analyzed children’s perceptions of teasing within their real world peer relationships through participants’ drawings and accompanying narratives. The case study research was approached from an ethic of listening to children to discover and uncover children’s perceptions and experiences with the phenomenon of peer teasing. Fifteen children from kindergarten to grade 2 participated in drawing and narrating their complex understandings of the multi-faceted aspects of peer teasing. The participants attended two 30-40 minute sessions of conversational interviews with the first session also involving drawing and narrating personal stories of teasing. The results of the study indicate the significance of teasing within the young peer relationship as well as several distinct perceptions and insights. Ultimately, these insights may help teachers to broaden curricular approaches within the school culture and enhance current theoretical conceptualizations of peer teasing.